Presentation And Outcome Of Infantile Hypertrophic Pyloric Stenosis: A Five Year Retrospective Study In Chittagong Medical College - Bhuiyan, Md Akbar Husain; Chowdhury, Tanvir Kabir; Rahman, MA Mushfiqur; Sajid, Md Minhajuddin; Farooq, Md Abdullah Al; Sarwar, Md Khurshid Alam; Das, Sahadeb Kumar; Habib, Md Golam (Journal of Chittagong Medical College Teachers' Association, 2014)
Infantile hypertrophic pyloric stenosis (IHPS) is the most common cause of gastric outlet obstruction in infants with a prevalence of 1.5 to 4.0 per 1000 live births. It has been suggested that the incidence is increasing. USG is the most useful method for diagnosis supplanting physical examination and pyloromyotomy is the time honored treatment option. A retrospective review of the patients of IHPS admitted in the department of Pediatric Surgery, Chittagong Medical College Hospital (CMCH) Chittagong, Bangladesh from January 2008 to December 2012 was done. Help was also taken from yearly departmental audits of 2008 to 2012. Data were analyzed with regard to occurrence, seasonal variation, gender variation, presentation, diagnosis, treatment and outcome. Statistical analysis was performed by the chi-square test, and mean and percentage values were calculated. P<0.05 was considered to be statistically significant. There were 42 patients of IHPS. Age range was 5 days to 1 year 8 months with mean age of 79 days. Male to Female ratio was 2.5:1. There was no significant difference between the rate of occurrence of IHPS and gender (P=0.5). There were 2 peaks on seasonal variations of IHPS during summer and winter but quarterly distribution was not statistically significant. Nonbilious vomiting was the most common clinical presentation and USG was the most useful investigation. Pyloromyotomy was done in all patients and persistent vomiting (24%) was the most common complication. The occurrence of IHPS was 0.29% of all admissions. There was no significant gender or seasonal variations. USG has replaced clinical examination as the most effective tool for diagnosis. Ramstedt pyloromytomy is still the choice of treatment on the basis of outcome. JCMCTA 2013 ; 24 (2): 9-13